Dynamic response for structural health monitoring of the Penang (I) cable-stayed bridge - Mohammed, M. I.; Sulaeman, Erwin; Mustapha, F. (Institute of Physics Publishing, 2017)
The paper discusses the dynamic response of the Penang (I) cable stayed bridge structure under various moving load representing typical traffic load of the bridge. The bridge has a total span of 440 m excluding the transition bridge that assumed to be not connected structurally to the main bridge structure. The bridge that links the fast growing Pinang Island and the Malaysian Mainland Peninsula has been known to be fully utilized which leads to the construction of Penang (II) bridge and now the third one. Due to highly traffic use of the bridge that may lead to reduction of the bridge design life, the dynamic response of the bridge becomes important to predict critical part of the bridge structure elements including the main girder and the 144 stay cables. The present study reveals that, due to flexible nature of the cable stayed bridge, the moving load that interacts with the natural dynamic characteristics of the bridge, gives significant stress increment compare to proportional static load especially when the moving load is un-symmetric. For this reason, several classes of typical vehicle passing the bridge with various vehicle speeds are investigated to demonstrate their effect on the bridge displacement, internal forces and stresses. The results can be used for further fatigue assessment of the bridge. © Published under licence by IOP Publishing Ltd.